PhyMill helps children with cerebral palsy - Safriza, Baharuddin; Nur Hartini, Mohd Hatta (2021)
PAYA BESAR, 10 December 2021 - PhyMill is an automatic exercise device to train walking movements for paediatric patients with a disability to control their position and activation due to damage to the developing brain or better known as cerebral palsy.